Rancang Bangun Sistem Navigasi Robot Beroda Pemandu Disabilitas Netra Menggunakan Metode Waypoint - Ahmad Rausan Fikri; Khairul Anam; Widya Cahyadi (Universitas Syiah Kuala, 2020)
Robotics has become a popular field of research for developing medical and human aids, including visually impaired people. This paper presents problem-solving of creating a robot that can guide visually impaired people outdoor using a Global Positioning System (GPS)-based navigation system with a waypoint method. This study uses Linkit ONE, which is equipped with a GPS as a determinant of the earth’s ordinate position, added with a compass module to determine the robot’s direction and a rotary encoder sensor to minimize the error of the robot’s position. There are two tests with four waypoints. Firstly, it is a test with no obstacles and holes. Secondly, it is the test with obstacles and holes. The first test results obtained an average error of waypoint-1 0.54 m(meters), waypoint-2 1.2 m, waypoint-3 1,9 m, and waypoint-4 1.7 m. Meanwhile, the second test results yielded an average error of waypoint-1 1.26 m, waypoint-2 2.18 m, waypoint-3 2.52 m, and waypoint-4 2,44 m. Therefore, the visual disability guidance robot with this waypoint method has good accuracy because the average error value of the robot is under a radius of 2 m when there are no obstacles and holes and under a radius of 3 m when there are obstacles and holes.